Developmental Anomalies In The Foetal Thyroid Gland - Devi, R. Raja Rajeshwari; Trivedi, Dipali Jayesh (Journal of Neonatal Surgery, 2025)
Introduction: Thyroid gland abnormalities are one in 2000 - 4000 new borns[1]. Key developmental anomalies encompass the persistence of the pyramidal lobe, thyroglossal cyst, agenesis, and ectopic thyroid [7]. Materials and methods: A total of 30 fetuses, aged between 12 and 40 weeks, were dissected. Out of 30 foetuses, 17 were females and 13 were male foetuses. Presence of pyramidal lobe, its length and extent were measured. The shape of thyroid gland, presence of levator glandulae thyroideae, abnormalities of isthmus and agenesis of thyroid gland were all assessed. Results: The presence of a pyramidal lobe was observed in 10 out of 30 fetuses, representing 33%. 4 out of 30 were arising from isthmus (13%). Among 12 male foetuses, 2 (6.6%) foetuses showed the presence of pyramidal lobe. Among 18 female foetuses, 8 (26.6%) showed the pyramidal lobe. 3 out of 30 (10%) showed agenesis of thyroid gland, 2 out of 30 (6.6%) revealed levator glandulae thyroideae and 2 out of 30 (6.6%) revealed accessory thyroid tissue. Most of the thyroid glands were butterfly shaped. 3 out of 30 (10%) were horseshoe shape, 3 out of 30 (10%) were W shaped (gland with separate lobes), 2 out of 30 (6.6%) had broader right lobe and 1 out of 30 (3.3%) had broader left lobe. Conclusion: Interventionists and surgeons must have a solid understanding of embryology, surgical anatomy, and thyroid gland variations to prevent complications and ensure safe, effective thyroidectomies